2019
DOI: 10.3390/condmat4010021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Temperature Annealing on Graphene with Nickel Contacts

Abstract: Graphene has shown great potential for ultra-high frequency electronics. However, using graphene in electronic devices creates a requirement for electrodes with low contact resistance. Thermal annealing is sometimes used to improve the performance of contact electrodes. However, high-temperature annealing may introduce additional doping or defects to graphene. Moreover, an extensive increase in temperature may damage electrodes by destroying the metal–graphene contact. In this work, we studied the effect of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The redshift in G band position is consistent with the influence of thermal annealing on the desorption of p-dopants from the graphene surface . These results demonstrate that vacuum annealing at the appropriate temperature is helpful to remove p-doping adsorbents on graphene, such as water vapor, O 2 , and other oxygen-containing molecules from the ambient environment. , Consequently, the V Dirac value shifts considerably toward 0 V (Figure S12a), and the mobility of these GFET devices increases (Figure S12b) due to reduced contamination on graphene surface . The remaining p-doping indicated by a nonzero V Dirac at ∼8 V can be attributed to SiO 2 defects. ,,, In addition, thermal annealing improves the mobility with an increase of ∼350 and ∼500 cm 2 V –1 s –1 for graphene patterns prepared by the conventional and microfluidic etching methods, respectively (Figure S12b).…”
Section: Results and Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The redshift in G band position is consistent with the influence of thermal annealing on the desorption of p-dopants from the graphene surface . These results demonstrate that vacuum annealing at the appropriate temperature is helpful to remove p-doping adsorbents on graphene, such as water vapor, O 2 , and other oxygen-containing molecules from the ambient environment. , Consequently, the V Dirac value shifts considerably toward 0 V (Figure S12a), and the mobility of these GFET devices increases (Figure S12b) due to reduced contamination on graphene surface . The remaining p-doping indicated by a nonzero V Dirac at ∼8 V can be attributed to SiO 2 defects. ,,, In addition, thermal annealing improves the mobility with an increase of ∼350 and ∼500 cm 2 V –1 s –1 for graphene patterns prepared by the conventional and microfluidic etching methods, respectively (Figure S12b).…”
Section: Results and Discussionsupporting
confidence: 68%
“…81 These results demonstrate that vacuum annealing at the appropriate temperature is helpful to remove p-doping adsorbents on graphene, such as water vapor, O 2 , and other oxygen-containing molecules from the ambient environment. 83,84 Consequently, the V Dirac value shifts considerably toward 0 V (Figure S12a), and the mobility of these GFET devices increases (Figure S12b) due to reduced contamination on graphene surface. 83 The remaining p-doping indicated by a nonzero V Dirac at ∼8 V can be attributed to SiO 2 defects.…”
Section: Resultsmentioning
confidence: 99%
“…The inhomogeneous distribution of stress and doping across the graphene patch might result in correlated variation in the height and position of Raman peaks to some extent. The impact of hightemperature annealing on graphene, such as enhanced hole doping or defects in graphene, has been widely reported on the basis of Raman spectroscopy studies [61][62][63][64] . It was also shown that annealing at temperatures below 500°C in vacuum results in a significant decrease in the "D peak" and "2D peak" due to annealing-induced enhanced doping in graphene, and annealing in a vacuum at temperatures of up to 1000°C results in a significant increase in the "2D peak" with a continuous decrease in the "D peak", indicating the partial removal of the defects and restoration of the damaged lattice 63 .…”
Section: Discussionmentioning
confidence: 99%
“…The cleaning and contact annealing of graphene at increased temperature levels examines the impact of the process on graphene attributes. A detailed comprehension of the changes happening during annealing is extremely significant, and thus has been thoroughly explored by researchers [ 141 ].…”
Section: Fabrication and Performance Of Graphene-based Membranesmentioning
confidence: 99%